THEORETICAL PREREQUISITE FOR THE DEVELOPMENT OF LIGHT INDUSTRY IN THE REPUBLIC OF KARAKALPAKSTAN (Global Economic Review: Journal of Economics, Policy, and Business Development, 2025)
The article discusses the features of the development of the light industry sector in the context of the emergence of global markets and the intensive use of information and communication technologies. The main attention is paid to the role of innovation in stimulating economic growth and prosperity, as well as overcoming social and environmental problems. The article also discusses the role of the state in stimulating innovation and overcoming potential problems and challenges. the experience of Uzbekistan in the development of an innovative economy is considered. The importance of light industry as a sector of the economy that creates new jobs and new innovative products is shown.